Doctrine of the revival of Russia as a political basis of development of the institute of presidency in democratic transit: new moments - V. V. Tyan (Управление)
The problem of developing the institute of presidency in the context of Russia’s revival has been considered in the article. The establishment of the presidency institute in 1991 marked the country’s transition to a democratic path of development. In the first decade, this task was carried out. In the content of Russia’s political reforms since the 2000s, it is possible to emphasize the solution of the problems of strengthening and developing the institute of presidency. The doctrine of the revival of Russia became the political basis for the development of the institution of the presidency. The second President of Russia, V. V. Putin became an indicator of this process. His commitment to the origins of Russian statehood helped create a goal-oriented team of strategic management. V. V. Putin's election as President of the Russian Federation for the fourth term was an expression of national trust. The presidency institute plays an important role in consolidating society. But the legitimacy of the President of the Russian Federation V. V. Putin was held in the context of the revival of Russia. The current President has contributed to the development of the presidency institute. In the system of state power, after adopting a series of measures, the institute of presidency was strengthened. Difficulties in the implementation of programs for the revival of Russia caused the use of neo-corporate and non-traditionalist management methods.In connection with the verticalization of power and the postponement of solving communication problems, the stability of the “Institute of the President - Government Authorities and Management - Network Society” system is weakened, reinforcing the deformation risks. It becomes necessary for the government to work closely with civil society in solving urgent domestic policy issues.The doctrine of the revival of Russia as a priority and the political basis for the development of the institute of presidency in the context of democratic legitimation retains a mobilization role in society.